Creating Cultural Empathy and Challenging Attitudes Through Indigenous Narratives Project : Evaluation Report for Edith Cowan University 4th December 2012. - Ramsay, Leeann; D'Antoine, Heather (Office for Learning and Teaching, 2012)
Evaluation report of a project that collected stories from Indigenous people about their experiences with health care services to enhance relationships and the development of lasting empathy. A national library of multi-media narratives of Indigenous experiences was established on the project website and is a powerful resource catering for different learning and teaching styles and addresses curriculum outcomes for a number of health disciplines. This project responded to the national priority of 'Closing the Gap' between the health outcomes of Indigenous and non-Indigenous people. The goal was to change the underlying attitudes of many health professionals that are known to negatively impact on their treatment of Indigenous people. This was achieved through the development and implementation of a story-based learning approach that helped students ',walk-in-the-shoes' of others. An expert, multi-professional team of West Australian Indigenous and non-Indigenous people lead the project, embedding better practices State-wide and nationally.